PENERAPAN KONSEP SMART SPACE DAN CONNECTED COMMUNITY PADA PERANCANGAN ESPORTS CENTER: Application of Smart Space and Connected Community Concepts in Esports Center Design - Putra, I Kadek Yogi Mahesa; Idedhyana, Ida Bagus; Primadewi, Siluh Putu Natha (Ganec Swara, 2025)
The development of esports as part of digital culture has created a demand for facilities that support competition, training, and digital community interaction. However, Denpasar City, as the center of the creative economy in Bali Province, does not yet have a dedicated facility that can optimally accommodate such activities. Therefore, this study focuses on the design specifications and the application of the Smart Space and Connected Community concepts in the design of an Esports Center in Denpasar City. The research employs a qualitative descriptive approach, with data collected through observation and literature study. The results indicate that the implementation of the Smart Space and Connected Community concepts produces a building that is not only functional and efficient but also reflects futuristic architectural characteristics through the use of reflective materials, dynamic lighting systems, and spatial configurations that foster digital interaction. Overall, the Esports Center is designed as a symbol of technological advancement and a new hub for the digital community in Denpasar City.